Customized Design of Aperiodic Liquid Crystal Grating for Generation of Multiple Optical Patterns - Chen Liu; Zhenghao Guo; Jun Wu; Dong Yuan; Guofu Zhou; Biao Tang; Huapeng Ye (Crystals, 2023)
Liquid crystal (LC) grating has drawn extensive attention due to its merits, including tunability, easy preparation process, cost effectiveness, and high diffraction efficiency. However, limited efforts have been made to explore LC grating for the generation of customized diffraction patterns, despite the fact that the patterning size of LC molecular director orientation has been tremendously reduced even to subwavelength scale via high-precision photoalignment techniques. Here, we propose a versatile method based on the binary particle swarm optimization algorithm to efficiently design aperiodic LC gratings for customized optical patterns generation, including needle beam, multi-foci, and hollow beam. The optical performance of the LC gratings was simulated using both the vectorial Rayleigh–Sommerfeld method (with discrete zero or π phase, in this article) and the actual director orientations. These results matched each other well, which proves the effectiveness of the optimization method based on discrete phase. This study paves the way for designing LC gratings with engineered functionalities, which may find applications in optical tweezers, laser delivery systems, and laser scanning imaging.